Blob, or the Novel at the Dawn of the Third Millennium: The Narrative Act Between Cinematography and the Media (Itinera, 2025)
The emergence of cinematography, radio, and Television in the early decades of the twentieth century revolutionized the relationship between the arts, not only the literary ones, and knowledge with the various economic and cultural elements that constitute mass society. At the core of this revolution was the narrative act, which until then had been considered the basic principle of all religious, philosophical, scientific, poetic, and artistic literature. From that moment on, the narrative act also became central to the media which, starting with cinema, began to recount not only the lives of rulers, the great nobility, politicians, and revolutions with Lenin, but also those of the common people, the marginalized, and the tramps, with Charlie Chaplin and Buster Keaton.The power of the narrative act, until then dominated by the individual rhetorical skill of writers, philosophers, scientists, and theologians, was from that moment employed by veritable teams of scriptwriters and directors, to narrate and impose stories and subjects upon the masses, attracting them also with effects like fear and wonder, appealing more to instincts than to rationality.The reaction of literature was almost immediate, as if those new arts had triggered a dialectic, generating the great masterpieces of the twentieth-century novel by James Joyce, Marcel Proust, Franz Kafka, Thomas Mann, and Robert Musil. Literary criticism immediately became aware of the fruitful relationship between literature and media; in its search for the main aesthetic values, it generated a proliferation of methods and orientations, mainly represented by structuralism and deconstructionism, which led it to a kind of paralysis, as two thinkers like Paul Valery and Walter Benjamin had anticipated. From all those studies, the only certain point, as critics such as Roland Barthes and Franco Brioschi noted, was the centrality of the narrative act, paradoxically applied even to destructuring programs like Blob, which built a plot with fragments of television and cinema. A challenge between media and literature that has now become a dialectic, because ugliness always ends up triggering the search for beauty, of which true art and true literature are always an expression.